Acquisition of a talent pool: AK Venture story - Mohd Saifudin, Adam; A. Jalil, Emy Ezura; Zainuddin, Nizamuddin; Bahaudin, Ahmad Yusni; Jamaludin, Roslan (Imbre, 2020)
Ninety per cent of world trade has been delivered by maritime. The significant role played by the maritime industry is undoubtedly crucial for world economic growth and prosperity. Therefore, AK Ventures had been chosen to portrait the dynamics of maritime management and operations. AK Ventures is unique because the company is only focused on Maritime, but they also diversified in other sectors in economic such as education (AK Academy), tourism (AK Travel) and property management (AK Property). Due to the vast activities of AK Ventures they can still perform well in all sectors with the minimum human resources and also the span of management of AK Ventures is not a so-called dynamic organisation but somewhat centralised management whereby the focus and the power of authority lie under one or two individuals. From the case it can be observed that AK Ventures does not have any proper strategic planning and human capital and retention plan. However, it can still perform with the full satisfied human resources (base on the interviews). This is very contrary to the human resource management studies. The focus of this case is on human resources planning, retaining, training and development of AK Academy. Applications of those theories and strategies are paramount in understanding, analysing, concluding and solving of the teaching notes.